ANALYSIS OF THE CONDITION OF THE THERMAL RESERVE ZONE OF THE BLAST FURNACE WHEN USING COAL COMPOSITIONS IN THE CHARGE (Modern Problems of Metallurgy, 2024)
The emergence and existence of zones in the blast furnace due to the laws of heat exchange are considered. In the middle zone of the blast furnace, the temperature of the outgoing gas stream remains relatively constant and no chemical processes occur in it. This is the "thermal reserve zone", the upper part of this zone - the "chemical reserve zone" is represented by wustite, which is not restored. The reserve of this zone is the formation of a gas phase. When additives are added to the charge of ore-coal compositions, iron oxides are reduced (t=1000 °C) by the reaction Fe2O3+C=Fe3O4+CO2 and carbon gasification СО2+С=2СО (Boudoir reaction). The resulting gas phase (CO) intensively reduces iron oxides. Composites for blast furnace smelting are produced from a mixture of blast furnace slurries with cement additives. The mixture is processed into coal pellets or briquettes. Blast furnace smelting at metallurgical plants in Ukraine, South Korea, and Japan has shown that the use of ore-coal composites is an effective additive to the charge of blast furnace smelting to reduce coke consumption. The coal-coal composite effect is based on the theory of "Coupling Phenomenon" between carbon and iron-containing materials in the composite pellet. Their interaction takes place, as research has shown, at temperatures of 250-420°C in a CO atmosphere. Taking into account the Boudoir reaction, the temperature in the thermal reserve zone of the blast furnace decreases by 80-200°C. Thus, in the chemical reserve zone, the recovery of wustite does not occur at 1000°C, but at 920-800°C, and it moves closer to the zones of iron and slag formation. The article analyzes thermograms in a blast furnace taking into account red coal deposits. Chemically, the reserve zone is located in the middle of the mine (from the slag surface) 11.2 m. With an increase in the consumption of composite in the charge (30%), the position of the reserve zone decreases from 11.2 to 6.2 m. The width between the thermograms of 1200°C - 1400°C is a characteristic zone of cohesion, with an increase in the consumption of the composite, it decreases from 2.1 m t (without loading the composite) to 0.9 m with a consumption of the composite of 30%.